USING MOTAD MODEL TO DETERMINE EFFICIENT PRODUCTION PLANS IN AL-KADHIMIYA AGRICULTURE DIVISION FARMS UNDER RISK AND UNCERTAINTY CONDITIONS 2012-2017 - Al-Nassr, R. Sh. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this research is to determine the current crop structure of Al- Kadhimiya Agriculture Division farms in order to determine the optimal use of the economic resources available for the purpose of achieving optimum crop structure that maximizes profits and total and net agricultural incomes. The study based  on the use of (LP) technique to determine the optimum agricultural production plan with the highest net income  using the statistical program (QSB), as well as (MOTAD) model was used to determine efficient agricultural plans (Income - Deviation) (E-A) and derive plans that take into account the risk margin of each farm plan using (MOTAD), as a model of alternative (LP) models for quadratic programming models, which used to determine the optimal farm production plans under conditions of risk and uncertainty, and sensitivity analysis was used of this model. The research has reached a number of conclusions, perhaps the most important of which is the matching of the research results to the research hypotheses. It was also found that the efficient plans that take into account the margin of risk have differed from the optimal plans which do not take into account the risk conditions which aim to maximize the expected income represented by the first plan obtained from using LP model. One of the most important recommendations of the research is that farmers should include the risk and uncertainty component within their plans to be more accurate and efficient by using mathematical models to analyze and determine efficient production plans under the risk and uncertainty conditions which represented by MOTAD model.